Al Insaf fi masail al khilaf bayna al nahwiyin, al basriyyin, wa alkufiyyin - Shaykh al Imam Kamaluddin Abi Barkat Abdurrahman ibn Muhammad ibn Abdullah ibn abi Sa'id al Anbari (Dar al Talai', 2005)
ws.c.1-3